Deteksi dan Klasifikasi Marka Pembatas Jalan Menggunakan Metode Voting dan Sampling - Pollo, Don E.D.G.; Aduatae, Daniel (Jurnal Media Elektro, 2013)
This paper explains the process of detecting and classifying of the lane as a computer vision application for safety driving on road. This lane is a sign to show the border for vehicle. The voting and sampling method are used to detect and classify this marka. By using the voting method, it can define the line equation that representing the lane position then the sampling method will define the type of the detected lane. To test these methods, it is used some condition as variation such as maneuver condition, lighting and lane breakage. The test results show that 93% of the detection and classification process can be done.